Superabsorbent polymer microparticles incorporating with crown ether for swelling-enhanced selective and rapid lithium capture - Ehsan Tabesh; Dylan Perry; Scott R. Smith; Pouya Rezai; Siu Ning Leung (Chemosphere, 2026)

Neurobehavioral and metabolic consequences of embryonic triphenyl phosphate exposure across the lifespan in zebrafish - Andrew B. Hawkey; Perry Piatos; Zade R. Holloway; Dilanaz Unal; Jonna Boyda; Richard T. Di Giulio; Edward D. Levin (Neurotoxicology and Teratology, 2026)

Critical choices for nature assessment design in emerging environmental markets - S.J. Capon; J. Brazil-Boast; J.A. Fitzsimons; J. McDonald; S.M. Prober; R. Trebilco; I. Cresswell; J. Perry; M. Bachmann; J. Pittock; C. Hunter; T.J. Eyre (Environmental Development, 2026)

Celebrating the Life of Dr. Andrew “Andy” Bakun - Francisco E. Werner; Jürgen Alheit; Vera Agostini; Steven Bograd; John Field; Anne B. Hollowed; Salvador Lluch‐Cota; Nate Mantua; R. Ian Perry; Ryan R. Rykaczewski; Frank Schwing; Justin Suca (Fisheries Oceanography, 2026)

Assessing hydrochar wash-water toxicity: screening strategies for reducing toxicity from food waste-derived hydrochars - Andres Sarrion; Jasmine R. Flora; Joseph R.V. Flora; Ramesh Goel; Lubo Liu; Perry J. Pellechia; Elena Diaz; Angel F. Mohedano; Nicole D. Berge (Waste Management, 2026)

The northern California current on fire: consequences of a widespread and persistent anomalous pyrosome bloom - Richard D. Brodeur; Dylan G.E. Gomes; Douglas L. Draper; Elizabeth A. Daly; Samantha M. Zeman; Moira Galbraith; R. Ian Perry; James J. Ruzicka; Roxanne R. Robertson (Progress in Oceanography, 2026)

Variable pH habitats could help prepare stone crabs for coastal acidification - Philip M. Gravinese; Hannah E. Craft; Alex Douwes; Gretchen S. Faraci; Morgan L. Jarrett; Shelby A. Perry; Chloe E. Potts; Emma C. Rosser; Abigail L. Smith; Alexis R. Trevillian; Christopher Moore; Kimberly K. Yates (Marine Biology, 2026)

Alaska visitors’ knowledge about invasive species in a warming arctic and sub-arctic - Michele Remer; Izabella R. Block; Elizabeth E. Perry; Jennifer I. Schmidt; Jianguo Liu (Biological Invasions, 2026)
As the climate warms and sea ice continues to melt, an increase in overall shipping traffic to the Arctic and to local communities is expected. Specifically, an increase in cruise ship traffic has led to higher numbers of visitors to the Arctic and sub-Arctic. As a secondary effect of increased human activity in this region, invasive species prevention and removal will become a priority, especially as species’ ranges continue to shift with the warming climate. Thus, it is important to have a baseline of visitor knowledge about invasive species in the region to promote robust monitoring. To evaluate visitor knowledge, we conducted visitor intercept surveys in three Alaskan communities that experience tourism. Results show that owning watercraft is associated with an increase in knowledge, but increased knowledge did not lead to any changes in behavior. In addition, increased invasive species knowledge did not differ between visitor groups. Our research demonstrates the need to consider the potential spread of invasive species due to tourism and a need to focus on both systemic policy changes and educational campaigns to encourage cleaning gear brought on travels.

Isolation and characterisation of cell wall polysaccharides from taewa (Māori potatoes; Solanum tuberosum L.) - Cara.A. Luiten; Simon F.R. Hinkley; Nick R. Roskruge; Saii A. Semese; Anne-Louise M. Heath; Tracy L. Perry; Nancy J. Rehrer; Ian M. Sims (Food Hydrocolloids, 2026)

Multi-year water level drawdown and wildlife grazing drive wetland vegetation succession - Kerstin Bouma; Gabriela Carrasco Oliva; Mats I. Douma; Perry Cornelissen; Mennobart R. van Eerden; Ralph J.M. Temmink; Bart A. Nolet; Elisabeth S. Bakker (Ecological Engineering, 2026)

Social and Ecological Context Shape Biological Invasions in Complex Landscapes - George L. W. Perry; James M. R. Brock; Cameron B. Guy; Casey Hamilton; Finnbar Lee; Dion L. Pou; Elizabeth Williams; Erica A. H. Smithwick (Current Landscape Ecology Reports, 2025)

Assessing future rainwater lens viability in coastal agricultural regions under climate change - Ilja America-van den Heuvel; Joost R. Delsman; Perry G.B. de Louw; Niko Wanders; Gualbert H.P. Oude Essink (Journal of Hydrology, 2025)

Reproductive risk of Neonicotinoids: A review of male rodent studies - Sumaiya S. Irfan; Veronica G. Sanchez; Michael S. Bloom; Helen B. Chin; Virginia Espina; Jenna R. Krall; Anna Z. Pollack; Lance A. Liotta; Melissa J. Perry (Environmental Research, 2025)

Functional characteristics of zooplankton bioregions along the cross-shelf gradient - Patrick R. Pata; Moira Galbraith; Kelly Young; Akash R. Sastri; R. Ian Perry; Brian P.V. Hunt (Progress in Oceanography, 2025)

Museum Genomics Reveals Temporal Genetic Stasis and Global Genetic Diversity in Arabidopsis thaliana - Lua Lopez; Patricia L. M. Lang; Stephanie Marciniak; Logan Kistler; Sergio M. Latorre; Asnake Haile; Eleanna Vasquez Cerda; Diana Gamba; Yuxing Xu; Patrick Woods; Mistire Yifru; Jeffrey Kerby; et al. (Molecular Ecology, 2025)
Global patterns of population genetic variation through time offer a window into evolutionary processes that maintain diversity. Over time, lineages may expand or contract their distribution, causing turnover in population genetic composition. At individual loci, migration, drift and selection (among other processes) may affect allele frequencies. Museum specimens of widely distributed species offer a unique window into the genetics of understudied populations and changes over time. Here, we sequenced genomes of 130 herbarium specimens and 91 new field collections of Arabidopsis thaliana and combined these with published genomes. We sought a broader view of genomic diversity across the species and to test if population genomic composition is changing through time. We documented extensive and previously uncharacterised diversity in a range of populations in Africa, populations that are under threat from anthropogenic climate change. Through time, we did not find dramatic changes in genomic composition of populations. Instead, we found a pattern of genetic change every 100 years of the same magnitude seen when comparing Eurasian populations that are 185 km apart, potentially due to a combination of drift and changing selection. We found only mixed signals of polygenic adaptation at phenology and physiology QTL. We did find that genes conserved across eudicots show altered levels of directional allele frequency change, potentially due to variable purifying and background selection. Our study highlights how museum specimens can reveal new dimensions of population diversity and show how wild populations are evolving in recent history.

Unique physiological and regulatory activity drives divergent toxin and non-toxin gene expression in rattlesnake accessory venom glands - Claire Kim; Sierra N. Smith; Siddharth S. Gopalan; Samuel R. Kerwin; Kaas Ballard; Blair W. Perry; Cara F. Smith; Anthony J. Saviola; Richard H. Adams; Stephen P. Mackessy; Todd A. Castoe (Toxicon, 2025)

Using New Zealand's late-Quaternary fossil record to estimate the past distribution and habitats of a relict species (kākāpō: Strigops habroptila) - Alexander P. Boast; Jamie R. Wood; Trevor H. Worthy; George L.W. Perry; Janet M. Wilmshurst (Quaternary Science Reviews, 2025)

Disentangling a genome-wide mosaic of conflicting phylogenetic signals in Western Rattlesnakes - Justin M. Bernstein; Yannick Z. Francioli; Drew R. Schield; Richard H. Adams; Blair W. Perry; Keaka Farleigh; Cara F. Smith; Jesse M. Meik; Stephen P. Mackessy; Todd A. Castoe (Molecular Phylogenetics and Evolution, 2025)

Seasonal monitoring of dissolved and particulate algal biotoxins in the northern Salish Sea using high performance liquid chromatography and tandem mass spectrometry - Andrew R.S. Ross; Béatrice Ip; Mackenzie Mueller; Blair Surridge; Harry Hartmann; Navinder Hundal; Nathan Matthews; Hayleigh Shannon; Melissa Hennekes; Akash Sastri; R. Ian Perry (Harmful Algae, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Was extinction of New Zealand's avian megafauna an unavoidable consequence of human arrival? - Sean Tomlinson; Mark V. Lomolino; Jamie R. Wood; Atholl Anderson; George L.W. Perry; Janet M. Wilmshurst; Jeremy J. Austin; Damien A. Fordham (Science of The Total Environment, 2025)

Water level drawdown and perennial vegetation impact litter decomposition in the sediment of a eutrophic wetland in the Netherlands - Kerstin Bouma; Mats I. Douma; G. F. Veen; Perry Cornelissen; Mennobart R. van Eerden; Elisabeth S. Bakker (Wetlands Ecology and Management, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Coral carbonate production across depth: homogenisation after bleaching? - Sivajyodee Sannassy Pilly; Ronan C. Roche; Ines D. Lange; Chris T. Perry; Andrew O. M. Mogg; Kathryn Dawson; John R. Turner (Coral Reefs, 2024)
Recurrent climate-driven warming events, which can induce severe coral bleaching and mortality on tropical reefs, are predicted to cause homogenisation of coral communities and loss of ecosystem functions in shallow reef systems (< 30 m). However, data documenting the variation in coral carbonate production across depth are limited. Here we explore differences in coral cover, community composition, coral colony size structure and carbonate production rates between two depths (10 m and 17.5 m) across four atolls in the remote Chagos Archipelago. We show higher coral carbonate production rates at 10 m (4.82 ± 0.27 G, where G = kg CaCO 3 m −2 yr −1 ) compared to sites at 17.5 m (3.1 ± 0.18 G). The main carbonate producers at 10 m consisted of fast-growing branching and tabular corals (mainly Acroporids) and massive corals (mainly Porites ), with high abundances of medium- and large-sized colonies. In contrast, coral carbonate production at 17.5 m was driven by slow-growing encrusting and foliose morphotypes and small colony sizes. Utilising a dataset following 6–7 years of recovery after the 2015–2017 bleaching event, our results show that depth-homogenisation of coral communities was temporary and carbonate production rates at 10 m depth recovered quicker at 3 of 4 studied atolls. The exception is Great Chagos Bank where slower recovery of branching and tabular corals at 10 m has led to a longer-lasting depth-homogenisation of carbonate production rates. The latter example cautions that more frequent bleaching events may drive increasing homogenisation of carbonate production rates across depth gradients, with implications for vital reef geo-ecological functions.

PBPK modeling demonstrates that exposure time adjustment is unnecessary for setting an acute manganese inhalation exposure guideline - Camarie S. Perry; Ann H. Verwiel; Tammie R. Covington; Deborah M. Proctor (Regulatory Toxicology and Pharmacology, 2024)

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

Producing 3D radargrams from orbital radar sounding data at Mars: History, results, methods, lessons and plans - Frederick J. Foss; Nathaniel E. Putzig; Bruce A. Campbell; Stewart A. Levin; Matthew R. Perry; John W. Holt; Michael S. Christoffersen; Isaac B. Smith; Gareth A. Morgan; Aaron T. Russell (Icarus, 2024)

A new numerical model of the HF antenna of the Mars Reconnaissance Orbiter’s (MRO) Shallow Radar (SHARAD) and first results from a test at a high-angle spacecraft roll - Alessandro DiCarlofelice; Piero Tognolatti; Fabrizio Bernardini; Renato Croci; Gareth A. Morgan; Matthew R. Perry; Nathaniel E. Putzig (Icarus, 2024)

Three-dimensional imaging of martian glaciated terrain using Mars Reconnaissance Orbiter Shallow Radar (SHARAD) observations - Matthew R. Perry; Aaron T. Russell; Megan B. Russell; Frederick J. Foss; Frank C. Chuang; Gareth A. Morgan; Zachary M. Bain; Bruce A. Campbell; Nathaniel E. Putzig (Icarus, 2024)

Science results from sixteen years of MRO SHARAD operations - Nathaniel E. Putzig; Roberto Seu; Gareth A. Morgan; Isaac B. Smith; Bruce A. Campbell; Matthew R. Perry; Marco Mastrogiuseppe (Icarus, 2024)

Dynamic development of the Athabasca Valles outflow system from volcanic facies and 15 m scale roughness - Russell C. Miller; Cyril Grima; Sean P.S. Gulick; Timothy A. Goudge; Aaron T. Russell; Matthew R. Perry; Nathaniel E. Putzig; Bruce A. Campbell (Icarus, 2024)

Effects of serta and sertb knockout on aggression in zebrafish (Danio rerio) - Michael Tea; Yihang Kevin Pan; Joshua G. R. Lister; Steve F. Perry; Kathleen M. Gilmour (Journal of Comparative Physiology A, 2024)

Within-field extrapolation away from a soil moisture probe using freely available satellite imagery and weather data - R. G. V. Bramley; E. M. Perry; J. Richetti; A. F. Colaço; D. J. Mowat; C. E. M. Ratcliff; R. A. Lawes (Precision Agriculture, 2024)
Recognition of the importance of soil moisture information to the optimisation of water-limited dryland cereal production has led to Australian growers being encouraged to make use of soil moisture sensors. However, irrespective of the merits of different sensing technologies, only a small soil volume is sensed, raising questions as to the utility of such sensors in broadacre cropping, especially given spatial variability in soil water holding capacity. Here, using data collected from contrasting sites in South Australia and Western Australia over two seasons, during which either wheat or barley were grown, we describe a method for extrapolating soil moisture information away from the location of a probe using freely-available NDVI time series and weather data as covariates. Relationships between soil moisture probe data, cumulative NDVI (ΣNDVI), cumulative net precipitation (ΣNP) and seasonal growing degree days (GDD) were significant ( P < 0.0001). In turn, these could be used to predict soil moisture status for any location within a field on any date following crop emergence. However, differences in ΣNDVI between different within-field zones did not fully explain differences in the soil moisture from multiple sensors located in these zones, resulting in different calibrations being required for each sensor or zone and a relatively low accuracy of prediction of measured soil moisture (R 2 adj ~ 0.4–0.7) which may not be sufficient to support targeted agronomic decision-making. The results also suggest that at any location within a field, the range of variation in soil moisture status down the soil profile on any given date will present as greater than the spatial variation in soil moisture across the field on that date. Accordingly, we conclude that, in dryland cereal cropping, the major value in soil moisture sensors arises from an enhanced ability to compare seasons and to relate similarities and differences between seasons as a guide to decision-making.

Calculating Nitrogen Uptake Rates in Forests: Which Components Can Be Omitted, Simplified, or Taken from Trait Databases and Which Must Be Measured In Situ? - Ray Dybzinski; Ella Segal; M. Luke McCormack; Christine R. Rollinson; Rosemary Mascarenhas; Perry Giambuzzi; Jamilys Rivera; Lucien Fitzpatrick; Caylin Wiggins; Meghan G. Midgley (Ecosystems, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Revealing the palaeoecology of silent taxa: selecting proxy species from associations in modern vegetation data - Jacqui M. M. Vanderhoorn; Janet M. Wilmshurst; Sarah J. Richardson; Thomas R. Etherington; George L. W. Perry (Journal of Biogeography, 2024)
Aim Species severely under‐represented in fossil pollen records leave gaps in interpretations and reconstructions of past vegetation. These ‘silent taxa’ leave little or no trace due to low pollen production, dispersal, preservation and taxonomic resolution. An approach for including them is through associating them with other species with reliable pollen representation. Here, we demonstrate a method for selecting such a proxy species for the Holocene using modern vegetation data. Location New Zealand. Taxon Beilschmiedia tawa (A.Cunn.) Benth. & Hook. F. ex Kirk (Lauraceae). Methods We used vegetation plot data to perform a pairwise co‐occurrence analysis of the New Zealand indigenous forest metacommunity to identify species with a strong positive association with Beilschmiedia tawa (tawa), a common tree severely under‐recorded in the pollen record. For those species, we then modelled their realised climatic niches to identify species with high niche overlap. We discuss how well those species could be interpreted from the Holocene fossil pollen record based on the representation of their pollen taxa. Results Knightia excelsa (rewarewa; Proteaceae) is a potential proxy for B. tawa in Holocene fossil pollen records, and other, range‐limited species may provide community‐specific proxies. We show combining resampling with sub‐sampling is a robust method for reducing the high false positive rate associated with large co‐occurrence analyses (1000+ sites) by limiting the sample size to 100 sites. Main Conclusions We show that the palaeoecology of silent taxa can be studied via proxy species, allowing their past distributions to be better understood. We highlight the importance of modelling many aspects of the realised niche to understand the usefulness and limitations of the silent–proxy association. Future research should focus on testing the underlying assumptions of the silent–proxy relationship so that models built on modern data can confidently be applied to palaeoecological data.

Water level drawdown induces a legacy effect on the seed bank and retains sediment chemistry in a eutrophic clay wetland - Kerstin Bouma; Elisabeth S. Bakker; Marleen Wilborts; Bjorn J.M. Robroek; Leon L. Lamers; Perry Cornelissen; Mennobart R. van Eerden; Ralph J.M. Temmink (Science of The Total Environment, 2024)

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Is our understanding of aquatic ecosystems sufficient to quantify ecologically driven climate feedbacks? - Corday R. Selden; Richard LaBrie; Laura C. Ganley; Daniel R. Crocker; Ohad Peleg; Danielle C. Perry; Hannah G. Reich; Matthew Sasaki; Patricia S. Thibodeau; Jana Isanta‐Navarro (Global Change Biology, 2024)
The Earth functions as an integrated system—its current habitability to complex life is an emergent property dependent on interactions among biological, chemical, and physical components. As global warming affects ecosystem structure and function, so too will the biosphere affect climate by altering atmospheric gas composition and planetary albedo. Constraining these ecosystem‐climate feedbacks is essential to accurately predict future change and develop mitigation strategies; however, the interplay among ecosystem processes complicates the assessment of their impact. Here, we explore the state‐of‐knowledge on how ecological and biological processes (e.g., competition, trophic interactions, metabolism, and adaptation) affect the directionality and magnitude of feedbacks between ecosystems and climate, using illustrative examples from the aquatic sphere. We argue that, despite ample evidence for the likely significance of many, our present understanding of the combinatorial effects of ecosystem dynamics precludes the robust quantification of most ecologically driven climate feedbacks. Constraining these effects must be prioritized within the ecological sciences for only by studying the biosphere as both subject and arbiter of global climate can we develop a sufficiently holistic view of the Earth system to accurately predict Earth's future and unravel its past.

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

Mid-season drain severity impacts on rice yields, greenhouse gas emissions and heavy metal uptake in grain: evidence from on-farm studies - Henry Perry; Daniela R. Carrijo; Aria H. Duncan; Scott Fendorf; Bruce A. Linquist (Field Crops Research, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Effect of Drought and Heavy Precipitation on CH4 Emissions and δ13C–CH4 in a Northern Temperate Peatland - Clarice R. Perryman; Carmody K. McCalley; Joanne H. Shorter; Apryl L. Perry; Natalie White; Angelica Dziurzynski; Ruth K. Varner (Ecosystems, 2024)

A cloudy forecast for species distribution models: Predictive uncertainties abound for California birds after a century of climate and land‐use change - John D. J. Clare; Perry de Valpine; Diana A. Moanga; Morgan W. Tingley; Steven R. Beissinger (Global Change Biology, 2024)
Correlative species distribution models are widely used to quantify past shifts in ranges or communities, and to predict future outcomes under ongoing global change. Practitioners confront a wide range of potentially plausible models for ecological dynamics, but most specific applications only consider a narrow set. Here, we clarify that certain model structures can embed restrictive assumptions about key sources of forecast uncertainty into an analysis. To evaluate forecast uncertainties and our ability to explain community change, we fit and compared 39 candidate multi‐ or joint species occupancy models to avian incidence data collected at 320 sites across California during the early 20th century and resurveyed a century later. We found massive (>20,000 LOOIC) differences in within‐time information criterion across models. Poorer fitting models omitting multivariate random effects predicted less variation in species richness changes and smaller contemporary communities, with considerable variation in predicted spatial patterns in richness changes across models. The top models suggested avian environmental associations changed across time, contemporary avian occupancy was influenced by previous site‐specific occupancy states, and that both latent site variables and species associations with these variables also varied over time. Collectively, our results recapitulate that simplified model assumptions not only impact predictive fit but may mask important sources of forecast uncertainty and mischaracterize the current state of system understanding when seeking to describe or project community responses to global change. We recommend that researchers seeking to make long‐term forecasts prioritize characterizing forecast uncertainty over seeking to present a single best guess. To do so reliably, we urge practitioners to employ models capable of characterizing the key sources of forecast uncertainty, where predictors, parameters and random effects may vary over time or further interact with previous occurrence states.

Biodegradable and conventional plastic packaging: Comparison of life cycle environmental impacts of poly(mandelic acid) and polystyrene - Harish K. Jeswani; Mitchell R. Perry; Michael P. Shaver; Adisa Azapagic (Science of The Total Environment, 2023)

Distinctive hospital and community resistomes in Scottish urban wastewater: Metagenomics of a paired wastewater sampling design - Hannah C. Lepper; Meghan R. Perry; Bryan A. Wee; David Wills; Hanne Nielsen; Saria Otani; Moray Simon; Frank M. Aarestrup; Mark E.J. Woolhouse; Bram A.D. van Bunnik (Science of The Total Environment, 2023)

Seasonal and regional variability of model-based zooplankton biomass in the Salish Sea and evaluation against observations - Karyn D. Suchy; Elise Olson; Susan E. Allen; Moira Galbraith; BethElLee Herrmann; Julie E. Keister; R. Ian Perry; Akash R. Sastri; Kelly Young (Progress in Oceanography, 2023)

Sensorimotor Cough Dysfunction in Cerebellar Ataxias - Emilie R. Lowell; James C. Borders; Sarah E. Perry; Avery E. Dakin; Jordanna S. Sevitz; Sheng-Han Kuo; Michelle S. Troche (The Cerebellum, 2023)

Domoic acid in Canadian Pacific waters, from 2016 to 2021, and relationships with physical and chemical conditions - R. Ian Perry; Nina Nemcek; Melissa Hennekes; Akash Sastri; Andrew R.S. Ross; Hayleigh Shannon; Ryan B. Shartau (Harmful Algae, 2023)

Seasonal and spatial dynamics of the phytoplankton community in the Salish Sea, 2015–2019 - Nina Nemcek; Melissa Hennekes; Akash Sastri; R. Ian Perry (Progress in Oceanography, 2023)

Drivers of shoreline change on Pacific coral reef islands: linking island change to processes - Meghna Sengupta; Murray R. Ford; Paul S. Kench; George L. W. Perry (Regional Environmental Change, 2023)
Reef islands are considered highly vulnerable to the impacts of anthropogenic climate change. While existing studies provide evidence of high dynamism and predominant stability over recent periods of sea-level rise, efforts to statistically link recorded morphological changes to processes are limited. We analyse shoreline changes across an expansive region of diverse oceanographic and climatic conditions and assess those observations relative to the processes potentially driving change. This record comprises 568 islands from 42 atolls spanning the western to the central Pacific Ocean from the Federated States of Micronesia, Marshall Islands, Kiribati and Tuvalu, and is one of the first robust attempts to statistically attribute the drivers of observed island changes within the past half-century. Our analyses demonstrate that island change and a range of its potential controls, including oceanographic, climatic and local-scale morphometric characteristics of reefs and islands, are not correlated, underscoring that no single variable could predict a uniform response across the study islands. The lack of association between sea-level rise and shoreline change on this large sample of islands addresses the common notion of a linear relationship between rising sea levels and magnitude of erosion in reef island systems. We emphasise the critical need to move from simplistic assessments of island change, highlight the importance of incorporating multiple predictors and the need for more computationally robust models.

Using environmental health dialogue in a Diné-centered approach for individualized results reporting in an environmental exposure study following the Gold King Mine Spill - Yoshira Ornelas Van Horne; Stephanie Russo Carroll; Karletta Chief; Nathan Z. Lothrop; Jennifer R. Richards; Mae-Gilene Begay; Perry H. Charley; Jani C. Ingram; Paloma I. Beamer (Environmental Research, 2023)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

Geography, environment, and colonization history interact with morph type to shape genomic variation in an Arctic fish - Sarah J. Salisbury; Robert Perry; Don Keefe; Gregory R. McCracken; Kara K. S. Layton; Tony Kess; Ian R. Bradbury; Daniel E. Ruzzante (Molecular Ecology, 2023)
Polymorphic species are useful models for investigating the evolutionary processes driving diversification. Such processes include colonization history as well as contemporary selection, gene flow, and genetic drift, which can vary between intraspecific morphs as a function of their distinct life histories. The interactive and relative influence of such evolutionary processes on morph differentiation critically informs morph‐specific management decisions and our understanding of incipient speciation. We therefore investigated how geographic distance, environmental conditions, and colonization history interacted with morph migratory capacity in the highly polymorphic fish species, Arctic Charr ( Salvelinus alpinus ). Using an 87 k SNP chip we genetically characterized recently evolved anadromous, resident, and landlocked charr collected from 45 locations across a secondary contact zone of three charr glacial lineages in eastern Canada. A strong pattern of isolation by distance across all populations suggested geographic distance principally shaped genetic structure. Landlocked populations had lower genetic diversities and higher genetic differentiation than anadromous populations. However, effective population size was generally temporally stable in landlocked populations in comparison to anadromous populations. Genetic diversity positively correlated with latitude, potentially indicating southern anadromous populations' vulnerability to climate change and greater introgression between the Arctic and Atlantic glacial lineages in northern Labrador. Local adaptation was suggested by the observation of several environmental variables strongly associating with functionally relevant outlier genes including a region on chromosome AC21 potentially associated with anadromy. Our results demonstrate that gene flow, colonization history, and local adaptation uniquely interact to influence the genetic variation and evolutionary trajectory of populations.

Treatment of acid mine drainage and chromium (VI) removal using synthesised chitosan composites blended with kenaf fibre and γ-Fe2O3 nanoparticles - C. N. Nkuna; E. R. Sadiku; G. Perry; B. Oboirien; M. K. Dludlu; C. Thompson (International Journal of Environmental Science and Technology, 2023)

Reprint of: COVID-19 messaging in U.S. state parks: Extensions of the outdoor recreation strategies and practices framework unmasked by the pandemic - Elizabeth E. Perry; Kimberly J. Coleman; Tatiana A. Iretskaia; Jordan M. Baer; Liesl F. Magnus; Peter R. Pettengill (Journal of Outdoor Recreation and Tourism, 2023)

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

In Memoriam: Timothy R. Parsons (1932–2022) - R. Ian Perry (Fisheries Oceanography, 2023)
One of the world's pre‐eminent marine scientists and the founding editor of Fisheries Oceanography , Professor Timothy (Tim) R. Parsons, passed away peacefully in hospital in April 2022. He was passionate about building a holistic understanding of how pelagic organisms are interconnected in the food‐webs of the sea, and about presenting alternative methods for the management of fisheries. For these activities and many others, he was the recipient of many international awards and honours. He had a profound influence on many students and colleagues, and leaves behind a foundational body of work on fisheries oceanography.

Novel rapid-acting sublingual nicotine tablet as a cigarette substitution strategy - Jed E. Rose; Frederique M. Behm; Tanaia L. Botts; David R. Botts; Perry N. Willette; Frank Vocci; John McCarty (Psychopharmacology, 2022)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Match/Mismatch Between Phytoplankton and Crustacean Zooplankton Phenology in the Strait of Georgia, Canada - Karyn D. Suchy; Kelly Young; Moira Galbraith; R. Ian Perry; Maycira Costa (Frontiers in Marine Science, 2022)
The Strait of Georgia, Canada, is an important region for numerous commercially and culturally important species (e.g., herring, salmon, and orcas), yet little is known about the links between lower trophic level (e.g. phytoplankton and zooplankton) phenology due to historical sampling gaps. Here, we present fourteen years (2003-2016) of data linking interannual variability in phytoplankton and zooplankton phenology in the Central Strait of Georgia, BC. Satellite-derived chlorophyll a (Chl a ) data were used to calculate spring bloom dynamics (bloom initiation, bloom intensity, and bloom magnitude). Average spring bloom initiation occurred during the last week of March in the Central Strait of Georgia. Bloom initiation occurred in mid-to-late February/early March during “early” Chl a bloom years (2004, 2005, and 2015) whereas initiation did not occur until the end of April during “late” bloom years (2007, 2008). Spring Chl a bloom initiation was significantly correlated with the North Pacific Gyre Oscillation (NPGO; r = 0.75, p < 0.01) and spring sea surface temperature (SST; r = -0.70, p < 0.01); spring blooms occurred earlier during warm years. When all environmental variables were considered together, NPGO best explained variations in spring bloom initiation (Adj R 2 = 0.53, p < 0.01) and bloom magnitude (Adj R 2 = 0.57, p < 0.01), whereas stratification best explained variations in bloom intensity (Adj R 2 = 0.38, p < 0.05). Early Chl a blooms were associated with high crustacean abundance (maximum of > 1000 ind m -3 ) but low biomass (37.5 mg m -3 ). Independent of the Chl a data, hierarchical cluster analysis revealed similar groupings of years for crustacean abundance data. Most notably, community composition in cluster Group 2 (2004, 2005, and 2015; early Chl a bloom years), was comprised of a higher proportion of small crustaceans (e.g. non-calanoid copepods) compared to the other cluster groups. To our knowledge, this study provides the first evidence linking early spring Chl a bloom timing to a shift in the crustacean community towards smaller taxa in response to multiple warm events in the Strait of Georgia. Our results show that early Chl a blooms may potentially result in a mismatch between phytoplankton and large energy-rich crustacean zooplankton, with lower abundances of the latter. In contrast, average Chl a bloom years were optimal for large-bodied euphausiids, whereas late Chl a blooms were a match for some crustaceans (e.g., medium calanoid copepods), but not others (e.g., large calanoid copepods and amphipods). We hypothesize that early bloom years may result in poorer feeding conditions for juvenile salmon and other predators in the region.

Gelatinous and soft-bodied zooplankton in the Northeast Pacific Ocean: Phosphorus content and potential resilience to phosphorus limitation - Florian Lüskow; Moira D. Galbraith; Brian P. V. Hunt; R. Ian Perry; Maarten Boersma; Evgeny A. Pakhomov (Hydrobiologia, 2022)

The importance of 1.5°C warming for the Great Barrier Reef - Jennifer K. McWhorter; Paul R. Halloran; George Roff; William J. Skirving; Chris T. Perry; Peter J. Mumby (Global Change Biology, 2022)
Tropical coral reefs are among the most sensitive ecosystems to climate change and will benefit from the more ambitious aims of the United Nations Framework Convention on Climate Change's Paris Agreement, which proposed to limit global warming to 1.5° rather than 2°C above pre‐industrial levels. Only in the latest Intergovernmental Panel on Climate Change focussed assessment, the Coupled Model Intercomparison Project phase 6 (CMIP6), have climate models been used to investigate the 1.5° warming scenario directly. Here, we combine the most recent model updates from CMIP6 with a semi‐dynamic downscaling to evaluate the difference between the 1.5 and 2°C global warming targets on coral thermal stress metrics for the Great Barrier Reef (GBR). By ~2080, severe bleaching events are expected to occur annually under intensifying emissions (shared socioeconomic pathway SSP5‐8.5). Adherence to 2° warming (SSP1‐2.6) halves this frequency but the main benefit of confining warming to 1.5° (SSP1‐1.9) is that bleaching events are reduced further to 3 events per decade. Attaining low emissions of 1.5° is also paramount to prevent the mean magnitude of thermal stress from stabilizing close to a critical thermal threshold (8 Degree Heating Weeks). Thermal stress under the more pessimistic pathways SSP3‐7.0 and SSP5‐8.5 is three to fourfold higher than the present day, with grave implications for future reef ecosystem health. As global warming continues, our projections also indicate more regional warming in the central and southern GBR than the far north and northern GBR.

Recursive Bayesian computation facilitates adaptive optimal design in ecological studies - Clinton B. Leach; Perry J. Williams; Joseph M. Eisaguirre; Jamie N. Womble; Michael R. Bower; Mevin B. Hooten (Ecology, 2022)
Optimal design procedures provide a framework to leverage the learning generated by ecological models to flexibly and efficiently deploy future monitoring efforts. At the same time, Bayesian hierarchical models have become widespread in ecology and offer a rich set of tools for ecological learning and inference. However, coupling these methods with an optimal design framework can become computationally intractable. Recursive Bayesian computation offers a way to substantially reduce this computational burden, making optimal design accessible for modern Bayesian ecological models. We demonstrate the application of so‐called prior‐proposal recursive Bayes to optimal design using a simulated data binary regression and the real‐world example of monitoring and modeling sea otters in Glacier Bay, Alaska. These examples highlight the computational gains offered by recursive Bayesian methods and the tighter fusion of monitoring and science that those computational gains enable.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Mechanical Response and Tolerance of the Anteriorly-Tilted Human Pelvis Under Vertical Loading - R. S. Salzar; E. M. Spratley; K. A. Henderson; P. C. Greenhalgh; J. Z. Zhang; B. J. Perry; J. A. McMahon (Annals of Biomedical Engineering, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Harbor Seals as Sentinels of Ice Dynamics in Tidewater Glacier Fjords - Jamie N. Womble; Perry J. Williams; Robert W. McNabb; Anupma Prakash; Rudiger Gens; Benjamin S. Sedinger; Cheyenne R. Acevedo (Frontiers in Marine Science, 2021)
Tidewater glaciers calve icebergs into the marine environment which serve as pupping, molting, and resting habitat for some of the largest seasonal aggregations of harbor seals ( Phoca vitulina richardii ) in the world. Although they are naturally dynamic, advancing and retreating in response to local climatic and fjord conditions, most tidewater glaciers around the world are thinning and retreating. Climate change models predict continued loss of land-based ice with unknown impacts to organisms such as harbor seals that rely on glacier ice as habitat for critical life history events. To understand the impacts of changing ice availability on harbor seals, we quantified seasonal and annual changes in ice habitat in Johns Hopkins Inlet, a tidewater glacier fjord in Glacier Bay National Park in southeastern Alaska. We conducted systematic aerial photographic surveys ( n = 55) of seals and ice during the pupping (June; n = 30) and molting (August; n = 25) periods from 2007 to 2014. Object-based image analysis was used to quantify the availability and spatial distribution of floating ice in the fjord. Multivariate spatial models were developed for jointly modeling stage-structured seal location data and ice habitat. Across all years, there was consistently more ice in the fjord during the pupping season in June than during the molting season in August, which was likely driven by seasonal variation in physical processes that influence the calving dynamics of tidewater glaciers. Non-pup harbor seals and ice were correlated during the pupping season, but this correlation was reduced during the molting season suggesting that harbor seals may respond to changes in habitat differently depending upon trade-offs associated with life history events, such as pupping and molting, and energetic costs and constraints associated with the events.

Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Jens M. Nielsen; Lauren A. Rogers; Richard D. Brodeur; Andrew R. Thompson; Toby D. Auth; Alison L. Deary; Janet T. Duffy‐Anderson; Moira Galbraith; J. Anthony Koslow; R. Ian Perry (Global Change Biology, 2021)
The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions.

Characterisation of LV myocardial exercise function by 2-D strain deformation imaging in elite adolescent footballers - Guido E. Pieles; Lucy Gowing; Diane Ryding; Dave Perry; Steven R. McNally; A. Graham Stuart; Craig A. Williams (European Journal of Applied Physiology, 2021)
Purpose Few data exist on the descriptions of LV myocardial mechanics and reserve during dynamic exercise of adolescent athletes. The aim of this study was to describe the LV myocardial and cardiopulmonary changes during exercise using 2-D strain deformation imaging. Methods Elite adolescent male football players ( n = 42) completed simultaneous cardiopulmonary exercise testing (CPET) and exercise echocardiography measurement of LV myocardial deformation by 2-D strain imaging. LV longitudinal and circumferential 2-D strain and strain rates were analyzed at each stage during incremental exercise to a work rate of 150 W. Additionally, exercise LV myocardial deformation and its relation to metabolic exercise parameters were evaluated at each exercise stage and in recovery using repeated measures ANOVA, linear regression and paired t tests. Results LV peak systolic baseline 2-D strain (longitudinal: − 15.4 ± 2.5%, circumferential: − 22.5 ± 3.1%) increased with each exercise stage, but longitudinal strain plateaued at 50 W (mean strain reserve − 7.8 ± 3.0) and did not significantly increase compared to subsequent exercise stages ( P > 0.05), whilst circumferential strain (mean strain reserve − 11.6 ± 3.3) significantly increased ( P < 0.05) throughout exercise up to 150 W as the dominant mechanism of exercise LV contractility increase. Regression analyses showed LV myocardial strain increased linearly relative to HR, VO 2 and O 2 pulse ( P < 0.05) for circumferential deformation, but showed attenuation for longitudinal deformation. Conclusion This study describes LV myocardial deformation dynamics by 2-D strain and provides reference values for LV myocardial strain and strain rate during exercise in adolescent footballers. It found important differences between LV longitudinal and circumferential myocardial mechanics during exercise and introduces a methodology that can be used to quantify LV function and cardiac reserve during exercise in adolescent athletes.

Cytokinin activity during early kernel development corresponds positively with yield potential and later stage ABA accumulation in field-grown wheat (Triticum aestivum L.) - Hai Ngoc Nguyen; Laura Perry; Anna Kisiala; Henry Olechowski; R. J. Neil Emery (Planta, 2020)

Limited genetic parallelism underlies recent, repeated incipient speciation in geographically proximate populations of an Arctic fish ( Salvelinus alpinus ) - Sarah J. Salisbury; Gregory R. McCracken; Robert Perry; Donald Keefe; Kara K.S. Layton; Tony Kess; Cameron M. Nugent; Jong S. Leong; Ian R. Bradbury; Ben F. Koop; Moira M. Ferguson; Daniel E. Ruzzante (Molecular Ecology, 2020)
The genetic underpinnings of incipient speciation, including the genomic mechanisms which contribute to morphological and ecological differentiation and reproductive isolation, remain poorly understood. The repeated evolution of consistently, phenotypically distinct morphs of Arctic Charr ( Salvelinus alpinus ) within the Quaternary period offer an ideal model to study the repeatability of evolution at the genomic level. Sympatric morphs of Arctic Charr are found across this species' circumpolar distribution. However, the specific genetic mechanisms driving this morph differentiation are largely unknown despite the cultural and economic importance of the anadromous morph. We used a newly designed 87k SNP chip to investigate the character and consistency of the genomic differences among sympatric morphs within three recently deglaciated and geographically proximate lakes in Labrador, Canada. We found genetically distinct small and large morph Arctic Charr in all three lakes consistent with resident and anadromous morphs, respectively. A degree of reproductive isolation among sympatric morphs is likely given genome‐wide distributions of outlier SNPs and high genome‐wide F ST s. Across all lakes, outlier SNPs were largely nonoverlapping suggesting a lack of genetic parallelism driving morph differentiation. Alternatively, several genes and paralogous copies of the same gene consistently differentiated morphs across multiple lakes suggesting their importance to the manifestation of morphs. Our results confirm the utility of Arctic Charr as a model for investigating the predictability of evolution and support the importance of both genetic parallelism and nonparallelism to the incipient speciation of Arctic Charr morphs.

Resolving marine dissolved organic phosphorus ( DOP ) composition in a coastal estuary - Douglas W. Bell; Perry J. Pellechia; Ellery D. Ingall; Claudia R. Benitez‐Nelson (Limnology and Oceanography, 2020)
A mechanistic understanding of dissolved organic phosphorus (DOP) utilization, and its role in the marine P cycle, requires knowledge of DOP molecular composition. In this study, a recently developed approach coupling electrodialysis and reverse osmosis with solution 31 P‐NMR analysis was used to examine DOP composition within a tidally dominated salt‐marsh estuary (North Inlet, South Carolina) over seasonal and tidal time frames. The isolation technique allowed for near complete recovery of the DOP pool (90% ± 13%; n = 12) with six broad compound classes quantified: phosphonates, phosphomonoesters, phosphodiesters, pyrophosphate, di‐ and tri‐phosphate nucleotides (nucleoP α ), and polyphosphate. Our results indicate that phosphomonoesters (ca. 61%) and phosphodiesters (ca. 31%) comprise the majority of the DOP pool, with relatively small contributions from pyrophosphates (ca. 4%), phosphonates (ca. 2%), nucleoP α (ca. 1%), and polyphosphates (ca. 1%). The study found no significant differences in DOP composition or concentration between tidal stages, despite significant tidal changes in dissolved organic nitrogen (DON):DOP stoichiometry. Significant seasonal variation was observed, with higher concentrations of phosphonates, nucleoP α , and monophosphates and lower phosphomonoester concentrations in Fall relative to all other seasons. We hypothesize that these seasonal variations reflect the balance between specific compound class seasonal production, lability, and local P demands associated with marine vs. terrestrial sources. Our results indicate that DOP composition exists at a dynamic equilibrium that is strongly conserved across diverse marine environments.

Gene flow creates a mirage of cryptic species in a Southeast Asian spotted stream frog complex - Kin O. Chan; Carl R. Hutter; Perry L. Wood; L. L. Grismer; Indraneil Das; Rafe M. Brown (Molecular Ecology, 2020)
Most new cryptic species are described using conventional tree‐ and distance‐based species delimitation methods (SDMs), which rely on phylogenetic arrangements and measures of genetic divergence. However, although numerous factors such as population structure and gene flow are known to confound phylogenetic inference and species delimitation, the influence of these processes is not frequently evaluated. Using large numbers of exons, introns, and ultraconserved elements obtained using the FrogCap sequence‐capture protocol, we compared conventional SDMs with more robust genomic analyses that assess population structure and gene flow to characterize species boundaries in a Southeast Asian frog complex ( Pulchrana picturata ). Our results showed that gene flow and introgression can produce phylogenetic patterns and levels of divergence that resemble distinct species (up to 10% divergence in mitochondrial DNA). Hybrid populations were inferred as independent (singleton) clades that were highly divergent from adjacent populations (7%–10%) and unusually similar (

The role of psychology in determining human–predator conflict across southern Kenya - Laura R. Perry; Tom P. Moorhouse; Andrew J. Loveridge; David W. Macdonald (Conservation Biology, 2020)
Conflict between people and carnivores can lead to the widespread killing of predators in retaliation for livestock loss and is a major threat to predator populations. In Kenya, a large, rural, pastoralist population comes into regular conflict with predators, which persist across southern Kenya. We explored the social and psychological backdrop to livestock management practices in this area in a process designed to be easy to use and suitable for use across large areas for the study of conflict and transboundary implementation of wildlife conflict reduction measures, focusing on community involvement and needs. We carried out fully structured interviews of livestock managers with a survey tool that examined how social and psychological factors may influence livestock management behavior. We compared survey responses on 3 sites across the study area, resulting in 723 usable responses. Efficacy of individuals’ livestock management varied between and within communities. This variation was partially explained by normative and control beliefs regarding livestock management. Individual livestock managers’ self‐reported management issues were often an accurate reflection of their practical management difficulties. Psychological norms, control beliefs, and attitudes differed among sites, and these differences partially explained patterns associated with conflict (i.e., variation in livestock management behavior). Thus, we conclude that a one‐size‐fits‐all approach to improving livestock management and reducing human–predator conflict is not suitable.

Temperature–Induced Hatch Failure and Nauplii Malformation in Antarctic Krill - Frances A. Perry; So Kawaguchi; Angus Atkinson; Sévrine F. Sailley; Geraint A. Tarling; Daniel J. Mayor; Cathy H. Lucas; R. King; A. Cooper (Frontiers in Marine Science, 2020)

The impact of acute and chronic exercise on Nrf2 expression in relation to markers of mitochondrial biogenesis in human skeletal muscle - Hashim Islam; Jacob T. Bonafiglia; Patrick C. Turnbull; Craig A. Simpson; Christopher G. R. Perry; Brendon J. Gurd (European Journal of Applied Physiology, 2020)

Seasonal and diel patterns in activity and habitat use by brook trout (Salvelinus fontinalis) in a small Newfoundland lake - D. Cote; B. Tibble; R. A. Curry; S. Peake; B. K. Adams; K. D. Clarke; R. Perry (Environmental Biology of Fishes, 2020)
Despite the challenges winter poses to salmonids inhabiting temperate and northern environments, there are relatively few studies that evaluate the factors that influence activity and habitat use during this season, particularly for lake environments that are ice-covered. This study examines brook trout depth distribution and movement (activity and range) in relation to temperature, light, and time of day across a 17-month period in a small lake in Newfoundland, Canada. Brook trout maintained elevated diurnal activity patterns throughout the year, despite seasonal changes in temperature, shifts in depth use, and prolonged, ice-induced darkness. Despite the tendency for relatively lower activity at night, brook trout remained active nocturnally, inferring a shift in foraging modes rather than a cessation of feeding. Winter movement velocities and ranges were less than other seasons but they occupied littoral areas that overlapped extensively with spring and fall core ranges. In contrast, summer core ranges of brook trout were principally comprised of areas with cooler water in the deep portion of the lake. As water temperature increased, daytime movement velocities increased in a log-linear fashion, whereas modeled nighttime movement velocity relationships with temperature were curvilinear and included the lowest movement velocities at 2–3 °C and the highest at the extremes of the occupied temperature range. The ability of brook trout to maintain diurnal activity patterns throughout a wide spectrum of environmental conditions suggests a strong behavioral and physiological capacity to adapt to their seasonally variable environment.

Floral Odors and the Interaction between Pollinating Ceratopogonid Midges and Cacao - Sarah E. J. Arnold; Samantha J. Forbes; David R. Hall; Dudley I. Farman; Puran Bridgemohan; Gustavo R. Spinelli; Daniel P. Bray; Garvin B. Perry; Leroy Grey; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2019)
Most plant species depend upon insect pollination services, including many cash and subsistence crops. Plants compete to attract those insects using visual cues and floral odor which pollinators associate with a reward. The cacao tree, Theobroma cacao , has a highly specialized floral morphology permitting pollination primarily by Ceratopogonid midges. However, these insects do not depend upon cacao flowers for their life cycle, and can use other sugar sources. To understand how floral cues mediate pollination in cacao we developed a method for rearing Ceratopogonidae through several complete lifecycles to provide material for bioassays. We carried out collection and analysis of cacao floral volatiles, and identified a bouquet made up exclusively of saturated and unsaturated, straight-chain hydrocarbons, which is unusual among floral odors. The most abundant components were tridecane, pentadecane, ( Z )-7-pentadecene and ( Z )-8-heptadecene with a heptadecadiene and heptadecatriene as minor components. We presented adult midges, Forcipomyia sp. (subgen . Forcipomyia ) , Culicoides paraensis and Dasyhelea borgmeieri, with natural and synthetic cacao flower odors in choice assays. Midges showed weak attraction to the complete natural floral odor in the assay, with no significant evidence of interspecific differences. This suggests that cacao floral volatiles play a role in pollinator behavior. Midges were not attracted to a synthetic blend of the above four major components of cacao flower odor, indicating that a more complete blend is required for attraction. Our findings indicate that cacao pollination is likely facilitated by the volatile blend released by flowers, and that the system involves a generalized odor response common to different species of Ceratopogonidae.

Developing a Social–Ecological–Environmental System Framework to Address Climate Change Impacts in the North Pacific - Steven J. Bograd; Sukyung Kang; Emanuele Di Lorenzo; Toyomitsu Horii; Oleg N. Katugin; Jackie R. King; Vyacheslav B. Lobanov; Mitsutaku Makino; Guangshui Na; R. Ian Perry; Fangli Qiao; Ryan R. Rykaczewski; et al. (Frontiers in Marine Science, 2019)

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

Rise Up, Get Tested, and Live: an Arts-Based Colorectal Cancer Educational Program in a Faith-Based Setting - Daniela B. Friedman; Swann Arp Adams; Heather M. Brandt; Sue P. Heiney; James R. Hébert; John R. Ureda; Jessica S. Seel; Courtney S. Schrock; Wilhelmenia Mathias; Vivian Clark-Armstead; Reverend Vernette Dees; Reverend Perry Oliver (Journal of Cancer Education, 2019)

A rapid, sensitive and inexpensive method for detection of grapevine red blotch virus without tissue extraction using loop-mediated isothermal amplification - J. Lucina Romero Romero; Gavriela Dena Carver; Patricio Arce Johnson; Keith L. Perry; Jeremy R. Thompson (Archives of Virology, 2019)

Census Estimates of Algal and Epiphytic Carbonate Production Highlight Tropical Seagrass Meadows as Sediment Production Hotspots - Chris T. Perry; Michael A. Salter; Kyle M. Morgan; Alastair R. Harborne (Frontiers in Marine Science, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Recurrent Hypoglycemia Exacerbates Cerebral Ischemic Damage in Diabetic Rats via Enhanced Post-Ischemic Mitochondrial Dysfunction - Vibha Shukla; Perry Fuchs; Allen Liu; Charles H. Cohan; Chuanhui Dong; Clinton B. Wright; Miguel A. Perez-Pinzon; Kunjan R. Dave (Translational Stroke Research, 2019)

Carbon dioxide enrichment alters predator avoidance and sex determination but only sex is mediated by GABAA receptors - Jean-Claude Abboud; Edgar A. Bartolome; Mayra Blanco; Annalise C. Kress; Ian Y. Ellis; Perry K. Yazzolino; Kamrin I. Sorensen; James R. Winslow; David A. Cleary; Hugh Lefcort (Hydrobiologia, 2019)

Novel ecological and climatic conditions drive rapid adaptation in invasive Florida Burmese pythons - Daren C. Card; Blair W. Perry; Richard H. Adams; Drew R. Schield; Acacia S. Young; Audra L. Andrew; Tereza Jezkova; Giulia I.M. Pasquesi; Nicole R. Hales; Matthew R. Walsh; Michael R. Rochford; Frank J. Mazzotti; et al. (Molecular Ecology, 2018)
Invasive species provide powerful in situ experimental systems for studying evolution in response to selective pressures in novel habitats. While research has shown that phenotypic evolution can occur rapidly in nature, few examples exist of genomewide adaptation on short “ecological” timescales. Burmese pythons ( Python molurus bivittatus ) have become a successful and impactful invasive species in Florida over the last 30 years despite major freeze events that caused high python mortality. We sampled Florida Burmese pythons before and after a major freeze event in 2010 and found evidence for directional selection in genomic regions enriched for genes associated with thermosensation, behaviour and physiology. Several of these genes are linked to regenerative organ growth, an adaptive response that modulates organ size and function with feeding and fasting in pythons. Independent histological and functional genomic data sets provide additional layers of support for a contemporary shift in invasive Burmese python physiology. In the Florida population, a shift towards maintaining an active digestive system may be driven by the fitness benefits of maintaining higher metabolic rates and body temperature during freeze events. Our results suggest that a synergistic interaction between ecological and climatic selection pressures has driven adaptation in Florida Burmese pythons, demonstrating the often‐overlooked potential of rapid adaptation to influence the success of invasive species.

A century of climate and land‐use change cause species turnover without loss of beta diversity in California’s Central Valley - Sarah A. MacLean; Andrea F. Rios Dominguez; Perry de Valpine; Steven R. Beissinger (Global Change Biology, 2018)
Climate and land‐use changes are thought to be the greatest threats to biodiversity, but few studies have directly measured their simultaneous impacts on species distributions. We used a unique historic resource—early 20th‐century bird surveys conducted by Joseph Grinnell and colleagues—paired with contemporary resurveys a century later to examine changes in bird distributions in California's Central Valley, one of the most intensively modified agricultural zones in the world and a region of heterogeneous climate change. We analyzed species‐ and community‐level occupancy using multispecies occupancy models that explicitly accounted for imperfect detection probability, and developed a novel, simulation‐based method to compare the relative influences of climate and land‐use covariates on site‐level species richness and beta diversity (measured by Jaccard similarity). Surprisingly, we show that mean occupancy, species richness and between‐site similarity have remained remarkably stable over the past century. Stability in community‐level metrics masked substantial changes in species composition; occupancy declines of some species were equally matched by increases in others, predominantly species with generalist or human‐associated habitat preferences. Bird occupancy, richness and diversity within each era were driven most strongly by water availability (precipitation and percent water cover), indicating that both climate and land‐use are important drivers of species distributions. Water availability had much stronger effects than temperature, urbanization and agricultural cover, which are typically thought to drive biodiversity decline.

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Multiple abiotic factors correlate with parallel evolution in Australian soil burrowing cockroaches - Perry G. Beasley‐Hall; Timothy R. C. Lee; Harley A. Rose; Nathan Lo (Journal of Biogeography, 2018)
Aim The ways in which abiotic factors contribute to parallel evolution—the evolution of similar, derived phenotypes in independent, closely related lineages—remain understudied. Australian cockroaches of the subfamilies Panesthiinae (“wood feeders”) and Geoscapheinae (“soil burrowers”) are two closely related groups that provide a striking example of parallel evolution of burrowing behaviour. The ancestral wood‐feeding panesthiines migrated from Asia ~20 million years ago before soil burrowing was independently acquired multiple times in the derived geoscapheines. Here, we investigate whether specific abiotic factors were associated with the parallel evolution of soil burrowing behaviour, and whether divergence events of geoscapheines from panesthiine ancestors are consistent with niche conservatism or divergence. Location The Australian mainland, including the areas in which selected Australian Panesthiinae and Geoscapheinae cockroach species are distributed. Methods We generated environmental niche models for members of the Australian Geoscapheinae and Panesthiinae using presence‐only data and abiotic variables related to temperature, precipitation, and soil composition from BioClim and the Australian Soil Resource Information System. We used an existing phylogenetic framework to compare environmental niche models and tested for niche conservatism versus divergence. Morphological convergence was assessed by a regression analysis and principal components analysis of leg segment and body dimensions in soil burrowers and wood feeders. Results We found no relationship between niche similarity and time since divergence, and only limited evidence for phylogenetic signal with respect to the environmental variables examined. We found that soil burrowing behaviour is consistently correlated with thirteen abiotic factors associated with aridity, including a wider range of temperatures and lower precipitation levels. Evidence for convergence in leg morphology and body dimensions across soil burrowers was found. Main conclusions Our results are consistent with soil burrowing behaviour evolving in response to ancient aridification events following the arrival of the Panesthiinae in Australia. Our results suggest a scenario of niche divergence between soil burrowers and each of their wood feeding sister taxa. There is evidence for morphological convergence on a “shovel‐like” protibiotarsus in the Geoscapheinae that would aid in burrowing into soil.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Monitoring dynamic spatio‐temporal ecological processes optimally - Perry J. Williams; Mevin B. Hooten; Jamie N. Womble; George G. Esslinger; Michael R. Bower (Ecology, 2018)
Population dynamics vary in space and time. Survey designs that ignore these dynamics may be inefficient and fail to capture essential spatio‐temporal variability of a process. Alternatively, dynamic survey designs explicitly incorporate knowledge of ecological processes, the associated uncertainty in those processes, and can be optimized with respect to monitoring objectives. We describe a cohesive framework for monitoring a spreading population that explicitly links animal movement models with survey design and monitoring objectives. We apply the framework to develop an optimal survey design for sea otters in Glacier Bay. Sea otters were first detected in Glacier Bay in 1988 and have since increased in both abundance and distribution; abundance estimates increased from 5 otters to >5,000 otters, and they have spread faster than 2.7 km/yr. By explicitly linking animal movement models and survey design, we are able to reduce uncertainty associated with forecasting occupancy, abundance, and distribution compared to other potential random designs. The framework we describe is general, and we outline steps to applying it to novel systems and taxa.

A novel grablovirus from non-cultivated grapevine (Vitis sp.) in North America - Keith L. Perry; Heather McLane; Jeremy R. Thompson; Marc Fuchs (Archives of Virology, 2018)

Archipelagic genetics in a widespread Caribbean anole - R. Graham Reynolds; Tanner R. Strickland; Jason J. Kolbe; Bryan G. Falk; Gad Perry; Liam J. Revell; Jonathan B. Losos (Journal of Biogeography, 2017)
Aim We examine the influence of fluctuating sea levels in a land‐bridge archipelago on the apportioning of intraspecific genetic diversity and divergence in the widespread Puerto Rican crested anole ( Anolis cristatellus ). We compare three alternative scenarios for genetic diversification in an archipelagic species that contrast the relative influences of periodic isolation versus island connectedness driven by fluctuating sea levels. Our approach combines information from geography and population genetics to assess the influence of island size, island isolation, island historical geography, and population genetic processes such as drift on the contemporary distribution of genetic variation within and among islands. Location The Puerto Rico Bank in the Caribbean focusing primarily on the Spanish, British and U.S. Virgin Islands. Methods We used nuclear and mitochondrial DNA sequences and microsatellite genotypes sampled from A. cristatellus populations to investigate: (1) the broad‐scale pattern of phylogeographical divergence across Puerto Rico Bank islands and (2) diversification within the Virgin Islands archipelago. For the first component, we used sequence data to reconstruct the relationships among 542 samples from across the species range. For the second component, we examined the relative influences of island size, isolation, and population genetic processes on the distribution of genetic diversity across the Virgin Islands. Results In the Virgin Islands, A. cristatellus is represented by a monophyletic clade except on the island of Vieques, where two divergent clades coexist. We found evidence for non‐equilibrium dynamics in the Virgin Islands, suggesting spatial population expansion during intraglacial periods of low sea level. Main conclusions We found limited evidence that periods of island isolation affected patterns of genetic diversity and differentiation. Instead, we found that the patterns of genetic diversity and divergence in A. cristatellus in the Virgin Islands archipelago are likely shaped by long‐term persistence in the region and periods of population spatial expansion.

Associations of human skeletal muscle fiber type and insulin sensitivity, blood lipids, and vascular hemodynamics in a cohort of premenopausal women - Gordon Fisher; Samuel T. Windham; Perry Griffin; Jonathan L. Warren; Barbara A. Gower; Gary R. Hunter (European Journal of Applied Physiology, 2017)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Methyl isonicotinate — a non-pheromone thrips semiochemical — and its potential for pest management - D. A. J. Teulon; M. M. Davidson; N. B. Perry; M. -C. Nielsen; C. Castañé; D. Bosch; J. Riudavets; R. W. H. M. van Tol; W. J. de Kogel (International Journal of Tropical Insect Science, 2017)

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

Investigating potential effects of zooplankton grazing on diatom-inferred drought reconstructions - Courtney R. Wigdahl-Perry; Jasmine E. Saros; Sherilyn C. Fritz; C. T. Hess (Hydrobiologia, 2017)

An integrated data model to estimate spatiotemporal occupancy, abundance, and colonization dynamics - Perry J. Williams; Mevin B. Hooten; Jamie N. Womble; George G. Esslinger; Michael R. Bower; Trevor J. Hefley (Ecology, 2017)
Ecological invasions and colonizations occur dynamically through space and time. Estimating the distribution and abundance of colonizing species is critical for efficient management or conservation. We describe a statistical framework for simultaneously estimating spatiotemporal occupancy and abundance dynamics of a colonizing species. Our method accounts for several issues that are common when modeling spatiotemporal ecological data including multiple levels of detection probability, multiple data sources, and computational limitations that occur when making fine‐scale inference over a large spatiotemporal domain. We apply the model to estimate the colonization dynamics of sea otters ( Enhydra lutris ) in Glacier Bay, in southeastern Alaska.

Air breathing and aquatic gas exchange during hypoxia in armoured catfish - Graham R. Scott; Victoria Matey; Julie-Anne Mendoza; Kathleen M. Gilmour; Steve F. Perry; Vera M. F. Almeida-Val; Adalberto L. Val (Journal of Comparative Physiology B, 2017)

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

A decision support tool for response to global change in marine systems: the IMBER ‐ ADA pT Framework - Alida Bundy; Ratana Chuenpagdee; Sarah R Cooley; Omar Defeo; Bernhard Glaeser; Patrice Guillotreau; Moenieba Isaacs; Makino Mitsutaku; R Ian Perry (Fish and Fisheries, 2016)
Global change is occurring now, often with consequences far beyond those anticipated. Although there is a wide range of assessment approaches available to address‐specific aspects of global change, there is currently no framework to identify what governance responses have worked and where, what has facilitated change and what preventative options are possible. To respond to this need, we present an integrated assessment framework that builds on knowledge learned from past experience of responses to global change in marine systems, to enable decision‐makers, researchers, managers and local stakeholders to: (i) make decisions efficiently; (ii) triage and improve their responses; and (iii) evaluate where to most effectively allocate resources to reduce vulnerability and enhance resilience of coastal people. This integrated assessment framework, IMBER ‐ ADA pT is intended to enable and enhance decision‐making through the development, a typology of case‐studies providing lessons on how the natural, social and governance systems respond to the challenges of global change. The typology is developed from a database of case‐studies detailing the systems affected by change, responses to change and, critically, an appraisal of these responses, generating knowledge‐based solutions that can be applied to other comparable situations. Fisheries, which suffer from multiple pressures, are the current focus of the proposed framework, but it could be applied to a wide range of global change issues. IMBER ‐ ADA pT has the potential to contribute to timely, cost‐effective policy and governing decision‐making and response. It offers cross‐scale learning to help ameliorate, and eventually prevent, loss of livelihoods, food sources and habitat.

Linking innovative measurement technologies (ConMon and Dataflow© systems) for high-resolution temporal and spatial dissolved oxygen criteria assessment - C. A. O’Leary; E. Perry; A. Bayard; L. Wainger; W. R. Boynton (Environmental Monitoring and Assessment, 2016)

A portrait of a sucker using landscape genetics: how colonization and life history undermine the idealized dendritic metapopulation - Sarah J. Salisbury; Gregory R. McCracken; Donald Keefe; Robert Perry; Daniel E. Ruzzante (Molecular Ecology, 2016)
Dendritic metapopulations have been attributed unique properties by in silico studies, including an elevated genetic diversity relative to a panmictic population of equal total size. These predictions have not been rigorously tested in nature, nor has there been full consideration of the interacting effects among contemporary landscape features, colonization history and life history traits of the target species. We tested for the effects of dendritic structure as well as the relative importance of life history, environmental barriers and historical colonization on the neutral genetic structure of a longnose sucker ( Catostomus catostomus ) metapopulation in the Kogaluk watershed of northern Labrador, Canada. Samples were collected from eight lakes, genotyped with 17 microsatellites, and aged using opercula. Lakes varied in differentiation, historical and contemporary connectivity, and life history traits. Isolation by distance was detected only by removing two highly genetically differentiated lakes, suggesting a lack of migration–drift equilibrium and the lingering influence of historical factors on genetic structure. Bayesian analyses supported colonization via the Kogaluk's headwaters. The historical concentration of genetic diversity in headwaters inferred by this result was supported by high historical and contemporary effective sizes of the headwater lake, T‐Bone. Alternatively, reduced allelic richness in headwaters confirmed the dendritic structure's influence on gene flow, but this did not translate to an elevated metapopulation effective size. A lack of equilibrium and upstream migration may have dampened the effects of dendritic structure. We suggest that interacting historical and contemporary factors prevent the achievement of the idealized traits of a dendritic metapopulation in nature.

Mitochondrial population structure and post‐glacial dispersal of longnose sucker Catostomus catostomus in Labrador, Canada: evidence for multiple refugial origins and limited ongoing gene flow - B. L. Langille; R. Perry; D. Keefe; O. Barker; H. D. Marshall (Journal of Fish Biology, 2016)
Two hundred and eighty‐seven longnose sucker Catostomus catostomus were collected from 14 lakes in Labrador, 52 from three lakes in Ontario, 43 from two lakes in British Columbia and 32 from a lake in Yukon; a total of 414 in all. The resulting 34 haplotypes (20 in Labrador) contained moderate haplotypic diversity ( h = 0·657) and relatively low nucleotide diversity ( π = 3·730 × 10 −3 . Mean ϕ ST (0·453, P C. catostomus populations across Canada, based on province, which was validated by the analysis and spatial analysis of molecular variance ( c. 80% variation between provinces). These results probably reflect the historical imprint of recolonization from different refugia and possibly indicate limited ongoing gene flow within provinces. A haplotype network revealed one major and two minor clades within Labrador that were assigned to the Atlantic, Beringian and Mississippian refugia, respectively, with tests of neutrality and mismatch distribution indicative of a recent population expansion in Labrador, dated between c. 3500 and 8300 years ago.

Response of temperate lakes to drought: a paleolimnological perspective on the landscape position concept using diatom-based reconstructions - Courtney R. Wigdahl-Perry; Jasmine E. Saros; Jennifer Schmitz; Randy Calcote; James Rusak; Dennis Anderson; Sara Hotchkiss (Journal of Paleolimnology, 2016)

Prediction of the Export and Fate of Global Ocean Net Primary Production: The EXPORTS Science Plan - David A. Siegel; Ken O. Buesseler; Michael J. Behrenfeld; Claudia R. Benitez-Nelson; Emmanuel Boss; Mark A. Brzezinski; Adrian Burd; Craig A. Carlson; Eric A. D'Asaro; Scott C. Doney; Mary J. Perry; Rachel H. R. Stanley; et al. (Frontiers in Marine Science, 2016)

An emerging role for gasotransmitters in the control of breathing and ionic regulation in fish - Steve Perry; Y. Kumai; C. S. Porteus; V. Tzaneva; R. W. M. Kwong (Journal of Comparative Physiology B, 2016)

Subcellular localization of grapevine red blotch-associated virus ORFs V2 and V3 - Tai Wei Guo; Deluxsika Vimalesvaran; Jeremy R. Thompson; Keith L. Perry; Björn Krenz (Virus Genes, 2015)

Legume, cropping intensity, and N-fertilization effects on soil attributes and processes from an eight-year-old semiarid wheat system - Justin K. O’Dea; Clain A. Jones; Catherine A. Zabinski; Perry R. Miller; Ilai N. Keren (Nutrient Cycling in Agroecosystems, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Development of 26 novel microsatellite makers for the round whitefish (Prosopium cylindraceum) and successful polymorphic cross-specific amplification of seven previously developed salmonid markers - Gregory R. McCracken; Kristen L. Wilson; Hilary T. Brewis; Meghan C. McBride; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Development and characterization of 36 novel microsatellite markers for lake chub (Couesius plumbeus) using illumina paired-end sequencing - Gregory R. McCracken; Hilary T. Brewis; Meghan C. McBride; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Development of 17 novel microsatellite markers for the longnose sucker (Catostomus catostomus) and successful cross-specific amplification of 14 previously developed markers from congeneric species - Gregory R. McCracken; Kristen L. Wilson; Ian Paterson; Robert Perry; Donald Keefe; Daniel E. Ruzzante (Conservation Genetics Resources, 2014)

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

Time-dependent effects of haloperidol on glutamine and GABA homeostasis and astrocyte activity in the rat brain - Glenn T. Konopaske; Nicolas R. Bolo; Alo C. Basu; Perry F. Renshaw; Joseph T. Coyle (Psychopharmacology, 2013)

Improvements to Rapfish: a rapid evaluation technique for fisheries integrating ecological and human dimensions a - T. J. Pitcher; M. E. Lam; C. Ainsworth; A. Martindale; K. Nakamura; R. I. Perry; T. Ward (Journal of Fish Biology, 2013)
This paper reports recent developments in Rapfish, a normative, scalable and flexible rapid appraisal technique that integrates both ecological and human dimensions to evaluate the status of fisheries in reference to a norm or goal. Appraisal status targets may be sustainability, compliance with a standard (such as the UN code of conduct for responsible fisheries) or the degree of progress in meeting some other goal or target. The method combines semi‐quantitative ( e.g . ecological) and qualitative ( e.g . social) data via multiple evaluation fields, each of which is assessed through scores assigned to six to 12 attributes or indicators: the scoring method allows user flexibility to adopt a wide range of utility relationships. For assessing sustainability, six evaluation fields have been developed: ecological, technological, economic, social, ethical and institutional. Each field can be assessed directly with a set of scored attributes, or several of the fields can be dealt with in greater detail using nested subfields that themselves comprise multidimensional Rapfish assessments ( e.g . the hierarchical institutional field encompasses both governance and management, including a detailed analysis of legality). The user has the choice of including all or only some of the available sustainability fields. For the attributes themselves, there will rarely be quantitative data, but scoring allows these items to be estimated. Indeed, within a normative framework, one important advantage with Rapfish is transparency of the rigour, quality and replicability of the scores. The Rapfish technique employs a constrained multidimensional ordination that is scaled to situate data points within evaluation space. Within each evaluation field, results may be presented as a two‐dimensional plot or in a one‐dimensional rank order. Uncertainty is expressed through the probability distribution of Monte‐Carlo simulations that use the c.l . on each original observation. Overall results of the multidisciplinary analysis may be shown using kite diagrams that compare different locations, time periods (including future projections) and management scenarios, which make policy trade‐offs explicit. These enhancements are now available in the R programming language and on an open website, where users can run Rapfish analyses by downloading the software or uploading their data to a user interface.

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

Human temperature regulation when given the opportunity to behave - Zachary J. Schlader; Blake G. Perry; M. Rahimi Che Jusoh; Lynette D. Hodges; Stephen R. Stannard; Toby Mündel (European Journal of Applied Physiology, 2013)

Sensitivity of survival to migration routes used by juvenile Chinook salmon to negotiate the Sacramento-San Joaquin River Delta - Russell W. Perry; Patricia L. Brandes; Jon R. Burau; A. Peter Klimley; Bruce MacFarlane; Cyril Michel; John R. Skalski (Environmental Biology of Fishes, 2013)

Estimating rates of biologically driven coral reef framework production and erosion: a new census-based carbonate budget methodology and applications to the reefs of Bonaire - C. T. Perry; E. N. Edinger; P. S. Kench; G. N. Murphy; S. G. Smithers; R. S. Steneck; P. J. Mumby (Coral Reefs, 2012)

Nitrogen fixation by pea and lentil green manures in a semi-arid agroecoregion: effect of planting and termination timing - Ann M. McCauley; Clain A. Jones; Perry R. Miller; Macdonald H. Burgess; Catherine A. Zabinski (Nutrient Cycling in Agroecosystems, 2012)

Identification of 104 rapidly-evolving nuclear protein-coding markers for amplification across scaled reptiles using genomic resources - Daniel M. Portik; Perry L. Wood; Jesse L. Grismer; Edward L. Stanley; Todd R. Jackman (Conservation Genetics Resources, 2012)

The safety of studies with intravenous Δ9-tetrahydrocannabinol in humans, with case histories - Michelle Carbuto; R. Andrew Sewell; Ashley Williams; Kim Forselius-Bielen; Gabriel Braley; Jacqueline Elander; Brian Pittman; Ashley Schnakenberg; Savita Bhakta; Edward Perry; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2012)

Feral genetically modified herbicide tolerant oilseed rape from seed import spills: are concerns scientifically justified? - Yann Devos; Rosemary S. Hails; Antoine Messéan; Joe N. Perry; Geoffrey R. Squire (Transgenic Research, 2012)

Compensatory regulation of acid–base balance during salinity transfer in rainbow trout (Oncorhynchus mykiss) - K. M. Gilmour; S. F. Perry; A. J. Esbaugh; J. Genz; J. R. Taylor; M. Grosell (Journal of Comparative Physiology B, 2012)

Drivers of region-wide declines in architectural complexity on Caribbean reefs - Lorenzo Alvarez-Filip; J. A. Gill; N. K. Dulvy; A. L. Perry; A. R. Watkinson; I. M. Côté (Coral Reefs, 2011)

FUS Immunogold Labeling TEM Analysis of the Neuronal Cytoplasmic Inclusions of Neuronal Intermediate Filament Inclusion Disease: A Frontotemporal Lobar Degeneration with FUS Proteinopathy - Tristan Page; Michael A. Gitcho; Sabrina Mosaheb; Deborah Carter; Sumi Chakraverty; Robert H. Perry; Eileen H. Bigio; Marla Gearing; Isidre Ferrer; Alison M. Goate; Nigel J. Cairns; Julian R. Thorpe (Journal of Molecular Neuroscience, 2011)

Strategies for selection marker-free swine transgenesis using the Sleeping Beauty transposon system - Daniel F. Carlson; John R. Garbe; Wenfang Tan; Mike J. Martin; John R. Dobrinsky; Perry B. Hackett; Karl J. Clark; Scott C. Fahrenkrug (Transgenic Research, 2011)

Green manure and phosphate rock effects on phosphorus availability in a northern Great Plains dryland organic cropping system - Terry L. Rick; Clain A. Jones; Richard E. Engel; Perry R. Miller (Organic Agriculture, 2011)

Spatial variation in porosity and skeletal element characteristics in apical tips of the branching coral Acropora pulchra (Brook 1891) - R. C. Roche; R. L. Abel; K. G. Johnson; C. T. Perry (Coral Reefs, 2011)

Regional differences in awareness and attitudes regarding genetic testing for disease risk and ancestry - Charles R. Jonassaint; Eunice R. Santos; Crystal M. Glover; Perry W. Payne; Grace-Ann Fasaye; Nefertiti Oji-Njideka; Stanley Hooker; Wenndy Hernandez; Morris W. Foster; Rick A. Kittles; Charmaine D. Royal (Human Genetics, 2010)

Polyphosphate in Trichodesmium from the low‐phosphorus Sargasso Sea - Elizabeth D. Orchard; Claudia R. Benitez-Nelson; Perry J. Pellechia; Michael W. Lomas; Sonya T. Dyhrman (Limnology and Oceanography, 2010)
Polyphosphate (polyP) is often considered to be the product of luxury uptake in areas of excess phosphorus (P), but can also accumulate in P‐depleted cells in response to P resupply. To test the hypothesis that polyP is present in phytoplankton from oligotrophic systems, the marine diazotroph Trichodesmium was collected from the low‐P surface waters of the Sargasso Sea and assayed with solid‐state 31 P nuclear magnetic resonance spectroscopy. Up to 25% of Trichodesmium cellular P was characterized as polyP, despite physiological data that indicated the colonies were P deplete. This was consistent with culture studies where there were high percentages of polyP under P‐deplete conditions. All Trichodesmium species examined had the genetic machinery to produce and degrade polyP. Trends in the amount of Trichodesmium polyP along the cruise transect showed that allocation of P to polyP was consistently high, and that the ratio of polyP : carbon varied with changes in temperature and mixed‐layer depth. It may be that Trichodesmium was taking advantage of pulses in P supply, and that polyP is a physiological fingerprint of this variability. Additionally, if polyP formation is a common trait in phytoplankton, polyP released from cells could be an additional bioavailable component of the dissolved organic P pool. Taken together, this study highlights the importance of polyP to P cycling and cellular P allocation even in oligotrophic regions.

Pervious and Impervious Urban Stormwater Runoff in a Rapidly Urbanizing Region: Occurrence of Fluoranthene and Pyrene - Rebecca R. James; Perry Wilbon; John P. DiVincenzo (Bulletin of Environmental Contamination and Toxicology, 2010)

Assessing Potential Risk to Alligators, Alligator mississippiensis, from Nutria Control with Zinc Phosphide Rodenticide Baits - Gary W. Witmer; John D. Eisemann; Thomas M. Primus; Jeanette R. O’Hare; Kelly R. Perry; Ruth M. Elsey; Phillip L. Trosclair (Bulletin of Environmental Contamination and Toxicology, 2010)

Deer Responses to Repellent Stimuli - Bruce A. Kimball; Jimmy Taylor; Kelly R. Perry; Christina Capelli (Journal of Chemical Ecology, 2009)

Clinical and molecular epidemiology of ciprofloxacin-susceptible MRSA encoding PVL in England and Wales - M. J. Ellington; C. Perry; M. Ganner; M. Warner; I. McCormick Smith; R. L. Hill; L. Shallcross; S. Sabersheikh; A. Holmes; B. D. Cookson; A. M. Kearns (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Tree canopy effect on grass and grass/legume mixtures in eastern Nebraska - Michael E. L. Perry; Walter H. Schacht; Gregory A. Ruark; James R. Brandle (Agroforestry Systems, 2009)

Combining remote sensing and economic analysis to support decisions that affect water productivity - P. J. G. J. Hellegers; R. Soppe; C. J. Perry; W. G. M. Bastiaanssen (Irrigation Science, 2009)

DNA-Protein Cross-Links in Erythrocytes of Freshwater Fish Exposed to Hexavalent Chromium or Divalent Nickel - Jim R. Kuykendall; Kyle L. Miller; Kristen M. Mellinger; Andrew J. Cain; Michael W. Perry; Michael Bradley; Eric J. Jarvi; Dennis J. Paustenbach (Archives of Environmental Contamination and Toxicology, 2009)

Observations of pigment and particle distributions in the western North Atlantic from an autonomous float and ocean color satellite - E. Boss; D. Swift; L. Taylor; P. Brickley; R. Zaneveld; S. Riser; M. J. Perry; P. G. Strutton (Limnology and Oceanography, 2008)
Profiling floats with optical sensors can provide important complementary data to satellite ocean color determinations by providing information about the vertical structure of ocean waters, as well as surface waters obscured by clouds. Here we demonstrate this ability by pairing satellite ocean color data with records from a profiling float that obtained continuous, high‐quality optical data for 3 yr in the North Atlantic Ocean. Good agreement was found between satellite and float data, and the relationship between satellite chlorophyll and floatderived particulate backscattering was consistent with previously published data. Upper ocean biogeochemical dynamics were evidenced in float measurements, which displayed strong seasonal patterns associated with phytoplankton blooms, and depth and seasonal patterns associated with an increase in pigmentation per particle at low light. Surface optical variables had shorter decorrelation timescales than did physical variables (unlike at low latitudes), suggesting that biogeochemical rather than physical processes controlled much of the observed variability. After 2.25 yr in the subpolar North Atlantic between Newfoundland and Greenland, the float crossed the North Atlantic Current to warmer waters, where it sampled an unusual eddy for 3 months. This anticyclonic feature contained elevated particulate material from surface to 1000‐m depth and was the only such event in the float's record. This eddy was associated with weakly elevated surface pigment and backscattering, but depthintegrated backscattering was similar to that previously observed during spring blooms. Such seldom‐observed eddies, if frequent, are likely to make an important contribution to the delivery of particles to depth.

Manipulating Beaver (Castor canadensis) Feeding Responses to Invasive Tamarisk (Tamarix spp.) - Bruce A. Kimball; Kelly R. Perry (Journal of Chemical Ecology, 2008)

Virtual observatories for space and solar physics research - Christopher C. Harvey; Michel Gangloff; Todd King; Christopher H. Perry; D. Aaron Roberts; James R. Thieman (Earth Science Informatics, 2008)

The Environmental Polymorphisms Registry: a DNA resource to study genetic susceptibility loci - Patricia C. Chulada; Heather L. Vahdat; Richard R. Sharp; Tracy C. DeLozier; Paul B. Watkins; Susan N. Pusek; Perry J. Blackshear (Human Genetics, 2008)

First EFSA experiences with monitoring plans - Detlef Bartsch; A. Gathmann; S. Hartley; N. B. Hendriksen; R. Hails; K. Lheureux; J. Kiss; S. Mesdagh; G. Neemann; J. Perry; S. Renckens; J. Schiemann; et al. (Journal of Consumer Protection and Food Safety, 2007)

Comparative evaluation of 15 serological assays for the detection of syphilis infection - M. J. Cole; K. R. Perry; J. V. Parry (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

In vivo pharmacological characterization of the structurally novel, potent, selective mGlu2/3 receptor agonist LY404039 in animal models of psychiatric disorders - Linda M. Rorick-Kehn; Bryan G. Johnson; Karen M. Knitowski; Craig R. Salhoff; Jeffrey M. Witkin; Kenneth W. Perry; Kelly I. Griffey; Joseph P. Tizzano; James A. Monn; David L. McKinzie; Darryle D. Schoepp (Psychopharmacology, 2007)

The cost of being an omnivore: mandible wear from plant feeding in a true bug - Bernard D. Roitberg; David R. Gillespie; Donald M. J. Quiring; Colleen R. Alma; Wade H. Jenner; Jennifer Perry; Jason H. Peterson; Maxence Salomon; Sherah VanLaerhoven (The Science of Nature, 2005)

Molecular distinction between true centric fission and pericentric duplication-fission - Jo Perry; Sara Nouri; Phung La; Art Daniel; Zhanhe Wu; Stuart Purvis-Smith; Emma Northrop; K. H. Andy Choo; Howard R. Slater (Human Genetics, 2005)

A new potato virus in a new lineage of picorna-like viruses - J. R. Thompson; K. L. Perry; W. De Jong (Archives of Virology, 2004)

Centric fission — simple and complex mechanisms - Jo Perry; Howard R. Slater; K. H. Andy Choo (Chromosome Research, 2004)

Phosphonates and particulate organic phosphorus cycling in an anoxic marine basin - C. R. Benitez-Nelson; Lauren O'Neill; Lauren C. Kolowith; Perry Pellechia; Robert Thunell (Limnology and Oceanography, 2004)
Total particulate phosphorus (TPP), particulate inorganic P (PIP), and particulate organic P (POP) concentrations were measured in a year‐long series of sediment trap samples collected throughout the oxic‐anoxic water column (275 m, 455 m, 930 m, and 1,255 m) of the Cariaco Basin. TPP, PIP, and POP fluxes varied seasonally and decreased significantly with depth, from 65 to 19 µmol TPP m −2 d −1 , 43 to 8 µmol PIP m −2 d −1 , and 22 to 11 µmol POP m −2 d −1 . Significant flux relationships (p 31 P nuclear magnetic resonance (NMR), and it was found that phosphonates, chemically and thermally inert compounds, are a significant fraction of the TPP pool. Furthermore, these compounds were preferentially removed relative to more bioavailable P esters during a low flux event. Their selective removal suggests that these compounds may be an unrecognized source of bioavailable P under anoxic conditions.

Postfire Management on Forested Public Lands of the Western United States - ROBERT L. BESCHTA; JONATHAN J. RHODES; J. BOONE KAUFFMAN; ROBERT E. GRESSWELL; G. WAYNE MINSHALL; JAMES R. KARR; DAVID A. PERRY; F. RICHARD HAUER; CHRISTOPHER A. FRISSELL (Conservation Biology, 2004)
Forest ecosystems in the western United States evolved over many millennia in response to disturbances such as wildfires. Land use and management practices have altered these ecosystems, however, including fire regimes in some areas. Forest ecosystems are especially vulnerable to postfire management practices because such practices may influence forest dynamics and aquatic systems for decades to centuries. Thus, there is an increasing need to evaluate the effect of postfire treatments from the perspective of ecosystem recovery. We examined, via the published literature and our collective experience, the ecological effects of some common postfire treatments. Based on this examination, promising postfire restoration measures include retention of large trees, rehabilitation of firelines and roads, and, in some cases, planting of native species. The following practices are generally inconsistent with efforts to restore ecosystem functions after fire: seeding exotic species, livestock grazing, placement of physical structures in and near stream channels, ground‐based postfire logging, removal of large trees, and road construction. Practices that adversely affect soil integrity, persistence or recovery of native species, riparian functions, or water quality generally impede ecological recovery after fire. Although research provides a basis for evaluating the efficacy of postfire treatments, there is a continuing need to increase our understanding of the effects of such treatments within the context of societal and ecological goals for forested public lands of the western United States.

Forest Structure and Fire Susceptibility in Volcanic Landscapes of the Eastern High Cascades, Oregon - DAVID A. PERRY; HUANG JING; ANDREW YOUNGBLOOD; DOUG R. OETTER (Conservation Biology, 2004)
Multidimensional forest health initiatives—those designed to restore and protect forest integrity in the large sense—require, among other things, a better understanding of the relationship between the structure of forests and (1) their susceptibility to wildfires outside the range of natural variability and (2) the level of treatment (if any) required to lower susceptibility into an acceptable range. Within the ponderosa pine zone (Pinus ponderosa Dougl. ex Laws.) on the eastern slopes of Oregon's Cascade Range, an average of 86% of trees >5 cm in diameter at breast height (dbh) were less than 101 years old, the density of young trees correlating negatively with the density of old trees (>150 yrs). Species composition differed significantly between age classes: 72% of trees older than 150 years were ponderosa pine, whereas 83% of trees younger than 101 years were either grand fir ( Abies grandis [Dougl.] Lindl.) or lodgepole pine ( Pinus contorta Dougl. ex). Loud Crown bulk density calculated to reflect the multiple canopy layer structure of these stands (CBDm) averaged 0.049 kg/m 3 , compared to 0.093 kg/m 3 using the standard approach ( p 2 = 0.92), implying that over certain ranges small changes in basal area result in relatively large changes in susceptibility (assuming that changes in basal area are due to addition or removal of smaller trees). Landsat thematic mapper correlates reasonably well with CBDm ( r 2 = 0.80) and may provide a tool for rapid risk assessment.

The Genetic Basis of Resistance to Diazinon in Natural Populations of Drosophila melanogaster - Fiona M. Pyke; Michael R. Bogwitz; Trent Perry; Adrian Monk; Philip Batterham; John A. McKenzie (Genetica, 2004)

Low doses of domoic acid during postnatal development produce permanent changes in rat behaviour and hippocampal morphology - T. A. Doucette; P. B. Bernard; H. Husum; M. A. Perry; C. L. Ryan; R. A. Tasker (Neurotoxicity Research, 2004)

The genetic architecture of correlations among growth‐related traits and male age at maturation in rainbow trout - C. J. Martyniuk; G. M. L. Perry; H. K. Mogahadam; M. M. Ferguson; R. G. Danzmann (Journal of Fish Biology, 2003)
Heritabilities and genetic correlations among growth‐related traits of two cultured strains (Rainbow Springs and Spring Valley) of rainbow trout Oncorhynchus mykiss were estimated using restricted maximum likelihood methods with a three‐generation pedigree. Heritability was high (>0·50 ± 0·03) for body mass and condition factor but moderate (0·35 ± 0·04) for age at sexual maturity in males. Body mass and age at sexual maturation were phenotypically correlated in the families of one experimental strain, Rainbow Springs, and had a positive genetic correlation (0·26 ± 0·03) across families from both test strains (Rainbow Springs and Spring Valley). This indicates that faster growing individuals were more likely to mature at 2 years of age than slower growing individuals in the two hatchery strains investigated. Microsatellite markers of body mass quantitative tract loci (QTL) were reconfirmed as being located on linkage groups B, G, N, 5 and new markers on Oi were detected. Some QTL effects were restricted to specific sampling dates suggesting temporal expression of QTL. QTL for condition factor were limited to linkage group G in both strains. Three suggestive QTL for precocious maturation mapped to similar regions as those for body mass in the Rainbow Springs families while no associations were evident in the Spring Valley families. The results suggest that these regions may play a role in the basis for genetic and phenotypic correlations between body mass and precocious maturation in this species.

Scale issues in marine ecosystems and human interactions - R. Ian Perry; Rosemary E. Ommer (Fisheries Oceanography, 2003)
Understanding the reciprocal interactions between humans and marine ecosystems has several fundamental difficulties, in particular compatible methodologies and different analytical scales. The issue of scale is central, as the scales chosen for studies of marine systems and human interactions can constrain recognition of the drivers and responses of these systems to global changes. The essential task is to discover how to combine social and natural science scale analyses to understand the impact of natural systems on people and the impact of people on natural systems. We identify characteristic spatial, temporal and organizational scales in marine ecosystems and human interactions, and the difficulties inherent in their cross‐disciplinary application. An approach is suggested focusing on communities of fish and fishers that makes explicit: (1) the need to manage marine resources in such a way as to encompass global to local scales; (2) recognition of the complementary nature of organizational scales between the natural and social sciences and use of appropriate natural science scales in the development of management policies; (3) the need to be aware of shifting temporal baselines and the representative nature of the data over time, for both social and natural sciences; and (4) caution regarding predictive models when humans are included. In terms of methodologies, good scale matches occur across large‐scale social and natural science models and surveys, but problems remain in small‐scale qualitative social studies and in cross‐scale studies. Cumulative case studies appear to provide the best approach, although ‘integrating up’ remains a challenge. Natural and social scientists need to work together to identify these issues of ecosystem processes and human interactions, and their appropriate scales.

The Impact of Tick Control on the Productivity of Indigenous Cattle under Ranch Conditions in Uganda - J. Okello-Onen; E.M. Tukahirwa; B.D. Perry; G.J. Rowlands; S.N. Nagda; G. Musisi; E. Bode; R. Heinonen; W. Mwayi; J. Opuda-Asibo (Tropical Animal Health and Production, 2003)

Use of telemetry in the development and application of biological criteria for habitat hydraulic modeling - D. A. Scruton; K. D. Clarke; L. M. N. Ollerhead; D. Perry; R. S. McKinley; K. Alfredsen; A. Harby (Hydrobiologia, 2002)

DIETS OF FIN, SEI, AND SPERM WHALES IN BRITISH COLUMBIA: AN ANALYSIS OF COMMERCIAL WHALING RECORDS, 1963–1967 - Rowenna D. Flinn; Andrew W. Trites; Edward J. Gregr; R. Ian Perry (Marine Mammal Science, 2002)
A bstract Diets of fin ( Balaenoptera physalus ), sei ( Balaenoptera borealis ), and sperm whales ( Physeter macrocephalus ) were estimated from the stomach contents of individuals killed along the British Columbia coast from 1963 to 1967. The dominant prey types of fin whales were euphausiids, with minor contributions from copepods and fish. Sei whale stomachs contained primarily copepods in three years, whereas euphausiids or a variety of fish dominated the diet in the other two years. Sperm whales consumed primarily North Pacific giant squid ( Moroteuthis robusta ), but secondary prey differed between males and females. Female sperm whales frequently consumed ragfish ( Icosteus spp.) and other fish, whereas the male diet also contained rockfish ( Sebastes spp.). The high abundance of euphausiids along the British Columbia coast likely contributed to the presence of a summer resident population of fin whales. The high abundance of large copepods farther north probably influenced the migration of sei whales through the offshore waters of British Columbia. Sperm whale stomach contents differed by sex reflecting location and possibly breeding behaviors.

The relationships among peak torque, mean power output, mechanomyography, and electromyography in men and women during maximal, eccentric isokinetic muscle actions - Joel T. Cramer; Terry J. Housh; Tammy K. Evetovich; Glen O. Johnson; Kyle T. Ebersole; Sharon R. Perry; Anthony J. Bull (European Journal of Applied Physiology, 2002)

Differentiation of Gut and Hepatic First-Pass Effect of Drugs: 1. Studies of Verapamil in Ported Dogs - Yong-Hee Lee; Barbara A. Perry; Hee-Sang Lee; Jeevan R. Kunta; John P. Sutyak; Patrick J. Sinko (Pharmaceutical Research, 2001)

High abundance of larval rockfish over Cobb Seamount, an isolated seamount in the Northeast Pacific - John F. Dower; R. Ian Perry (Fisheries Oceanography, 2001)
The larval fish community in the region of Cobb Seamount (500 km west of Oregon) is dominated by myctophid species commonly encountered in the subarctic North Pacific. However, during a survey in June 1992, the ichthyoplankton community within 30 km of the seamount summit was almost completely dominated by larvae of various rockfish ( Sebastes ) species. Given their very small size (and hence very young age) and the fact that they occurred only rarely in samples collected > 30 km from the seamount summit, we conclude that these Sebastes larvae were produced locally over Cobb Seamount. Previous studies have shown that the Cobb fish fauna is dominated by various Sebastes spp. and that, unlike other fish present on the seamount, the rockfish populations may be self‐recruiting. We suggest that a persistent clockwise (i.e. downwelling) eddy, consistent with a stratified Taylor cone, plays a critical role in retaining larval rockfish over Cobb Seamount and may contribute to the process of self‐recruitment. The key to the success of rockfish on Cobb and other shallow Northeast Pacific seamounts seems to be linked to their viviparous life history.

Developing jellyfish strategy hypotheses using circulation models - Donald R. Johnson; Harriet M. Perry; W. David Burke (Hydrobiologia, 2001)

Early Secondary Succession in Bottomland Hardwood Forests of Southeastern Virginia - DAVID R. SPENCER; JAMES E. PERRY; GENE M. SILBERHORN (Environmental Management, 2001)

Mechanomyographic and electromyographic responses during submaximal cycle ergometry - Terry J. Housh; Sharon R. Perry; Anthony J. Bull; Glen O. Johnson; Kyle T. Ebersole; Dona J. Housh; Herbert A. deVries (European Journal of Applied Physiology, 2000)

Environmental influences on the availability of smooth pink shrimp, Pandalus jordani , to commercial fishing gear off Vancouver Island, Canada - R. Ian Perry; James A. Boutillier; Michael G.G. Foreman (Fisheries Oceanography, 2000)
Short time scale (less than seasonal) variability in commercial catch rates of smooth pink shrimp, Pandalus jordani, off the west coast of Vancouver Island, Canada, was examined in relation to changes in environmental conditions. Catch per unit of effort (CPUE) data were used as a proxy for catchability to identify environmental conditions affecting the availability of shrimp to the two main gear types in this fishery: otter trawls and beam trawls. Correlogram analyses of the 1996 CPUE (log‐transformed) data from each gear type, and autocorrelation analyses of wind stress, tidal current speed, sea surface temperature and salinity, and hours of bright sunshine (the latter three as residuals from their seasonal trends) for 1996 indicated a mean decorrelation time scale of 7.7 days. This was used to construct smoothed time series of these CPUE and environmental data for 1996. Multiple regression analyses with CPUE as the dependent variable and the environmental data as independent variables were significant, explaining 44% of the variability in otter‐trawl data and 35% of the beam‐trawl variability. Three hypotheses are proposed to explain these results, involving interactions between the shrimp’s behaviour and environmental conditions. A significant proportion of the within‐season variability in CPUE (and therefore in the availability of shrimp to fishing gear) for P. jordani off Vancouver Island can result from variations in environmental conditions which, if included in stock analyses, should reduce the variability of population abundance estimates.

Sex differences in sensorimotor gating of the human startle reflex: all smoke? - N. R. Swerdlow; M. A. Geyer; P. L. Hartman; J. Sprock; P. P. Auerbach; K. Cadenhead; W. Perry; D. L. Braff (Psychopharmacology, 1999)

A framework for providing scientific advice for the management of new and developing invertebrate fisheries - R. Ian Perry; Carl J. Walters; James A. Boutillier (Reviews in Fish Biology and Fisheries, 1999)

Population biology of a failed invasion: Paleolimnology of Daphnia exilis in upstate New York - Nelson G. Hairston; Linda J. Perry; Andrew J. Bohonak; Meghan Q. Fellows; Colleen M. Kearns; Daniel R. Engstrom (Limnology and Oceanography, 1999)
Viable diapausing eggs of Daphnia exilis , a species within the Daphnia similis species complex, occur in sediments of Onondaga Lake, New York. The discovery of this species, which otherwise occurs exclusively in temporary saline ponds in southwestern North America, represents a range extension of 1,000 km. 210 Pb‐dating of the sediments containing diapausing eggs indicates that D. exilis was present in Onondaga Lake between the mid‐1920s and the early 1980s. The species' introduction, successful colonization, and subsequent disappearance from the water column correspond temporally with distinct events in the history of industrial activity along the shores of the lake and with the paleoecological record of this activity deposited in Onondaga Lake sediments. Only the most recently deposited diapausing eggs (late 1970s to early 1980s) hatch during laboratory incubation; older eggs may not be viable because of toxic concentrations of mercury pollution in older sediments. The D. exilis eggs that have hatched have had strikingly low genetic (allozyme) variation in comparison with the variation documented for populations in the southwestern United States by Hebert and Finston (1993). Exploration of various invasion scenarios through simulated introduction of genotypes from the southwestern United States suggests that a single genotype established the D. exilis population in Onondaga Lake. These observations document the ecological and microevolutionary patterns associated with an invasion by an exotic crustacean that currently persists only in the sediment egg bank.

Population dynamics of ticks on indigenous cattle in a pastoral dry to semi-arid rangeland zone of Uganda - J. Okello-Onen; E.M. Tukahirwa; B.D. Perry; G.J. Rowlands; S.M. Nagda; G. Musisi; E. Bode; R. Heinonen; W. Mwayi; J. Opuda-Asibo (Experimental and Applied Acarology, 1999)

The effect of leg flexion angle on the mechanomyographic responses to isometric muscle actions - Kyle T. Ebersole; Terry J. Housh; Glen O. Johnson; Tammy K. Evetovich; Douglas B. Smith; Sharon R. Perry (European Journal of Applied Physiology, 1998)

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

Temperature change and complex dynamics - X. Zhou; J. N. Perry; I. P. Woiwod; R. Harrington; J. S. Bale; S. J. Clark (Oecologia, 1997)

Nonconceptive Sexual Behavior in Bonobos and Capuchins - Joseph H. Manson; Susan Perry; Amy R. Parish (International Journal of Primatology, 1997)

Increased metabolic cost of maintenance in hybrids of the stone crabs Menippe mercenaria and M. adina - C. A. Combs; R. P. Henry; T. M. Bert; H. M. Perry; M. West (Marine Biology, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Electrophysiological Responses of Male Potato Cyst NematodesGlobodera rostochiensis and G. pallidato Some Chemicals - Ekaterini Riga; Roland N. Perry; John Barrett; Mike R. L. Johnston (Journal of Chemical Ecology, 1997)

The effect of climate change on an aphid–coccinellid interaction - D.J. SKIRVIN; J.N. PERRY; R. HARRINGTON (Global Change Biology, 1997)
A model (Carter et al. 1982) that described the population dynamics of Sitobion avenae was modified and extended to include the population dynamics of the aphidophagous coccinellid, Coccinella septempunctata. The model was run under three different temperature regimes, corresponding to different degrees of warmth in typical English summers, and, in addition, within‐regime temperature was altered, to predict the likely effects of climatic change on the interaction between the aphid and coccinellid. The model predicts that the presence of coccinellids causes a reduction in the number of aphids of between 40 and 60 percent, and advances the Julian date of their maximum numbers. The model also predicts that an increase in temperature within a regime results in smaller maximum and total numbers of aphids. In the presence of coccinellids, aphids were predicted to be most successful in moderately warm summers. The predicted maximum number of coccinellids was not greatly affected by temperature, but their total number was, in a complex way. The greatest effect of coccinellids to reduce both maximum and total aphid numbers was predicted to occur for relatively hot summers. A sensitivity analysis was used to identify those aspects of the coccinellid submodel that require possible refinement.

Lipids of the marine bacterium Flexibacter polymorphus - R. B. Johns; G. J. Perry (Archives of Microbiology, 1977)

Alamo: A new early-maturing, high-yielding, widely adapted potato variety - R. V. Akeley; Bruce Perry; R. D. Peel (American Journal of Potato Research, 1968)

Redskin, a new red variety of potato resistant to scab, with high yielding ability, and adapted to growing conditions in the south - R. V. Akeley; Bruce A. Perry; Allen E. Schark (American Journal of Potato Research, 1961)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Mechanical damage to potatoes during harvesting and handling operations in the red river valley of minnesota and North Dakota - R. E. Nylund; Perry Hemphill; J. M. Lutz; Harold Sorenson (American Journal of Potato Research, 1955)